OPTIMALISASI PRODUKSI ASESORIS SEPEDA MOTOR DI CV BOUDY MOTOR MENGGUNAKAN METODE SIMPLEKS PROGRAM LINEAR DENGAN SOFTWARE POM-QM - mustaqim mustaqim; Mukhammad Ubaidillah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
CV Boudy Motor is one of the automotive businesses engaged in manufacturing, production of variations of motorcycle accessories. Demand, inventory and production processes constitute a package system in the productivity of industrial profits. This study aims to determine optimal production and profit using the simplex linear program method with POM-QM software. The calculation results, the optimal production for footstep products is 1,000 pcs and a variation ruler is 2,600 pcs. The total overall profit obtained by CV Boudy Motor from footstep products and variation rulers for per day is Rp. 6,900,000 and for per month with 26 days of active period is Rp. 179,000,000 assuming the profit is in accordance with the goal function and fixed constraint function.